Faktor-Faktor Determinan dalam Produktivitas Karyawan di BP Swalayan: Studi Analisis Kinerja pada Usaha Ritel - Ulya, Zikriatul; Dewi , Meutia (Jurnal Manajemen dan Keuangan, 2023)
This study aims to analyze the influence of leadership style, work discipline, motivation, income, on morale in improving employee performance at BP Swalayan in Peureulak District. The data used in this studyis primary data using a questionnaire and distributed to the respondents in the study. The data analysis technique in this study uses Partial Least Square (PLS). The results of this studyshows that the variables of work discipline, motivation, income have no effect on employee performance. For work discipline and motivation variables have no effect on morale. Meanwhile, leadership style and work enthusiasm affect employee performance. Leadership style and income variables influence work morale. The variables of work discipline and motivation have no effect on morale through employee performance. Leadership style and income variables affect morale through employee performance. The adjusted R Square value of the variable leadership style, work discipline, motivation, income, and morale is able to explain the employee performance variable of 85.3% and the Adjusted R Square Value of the morale variable is 40.5%.